An education-based approach for enabling the sustainable development gear. (June 2020) - Mora, Higinio; Pujol-López, Francisco A.; Mendoza-Tello, Julio C.; Morales-Morales, Mario Raul
Abstract: The advances in Information and Communication Technologies (ICTs), together with social commerce initiatives, collaborative economy and education, are working together to move the gears of sustainable development. All of these aspects have the potential to revolutionize social business and contribute to future sustainable development. In the past few years, the economy has seen the emergence of modern business models and innovative ideas, mainly driven by ICT. Concepts such as social commerce, collaborative economy and virtual currencies establish new business models, in which participants seek equity exchanges, trust, cooperation, and a better redistribution of incomes. Education cannot be exempted from this evolution. Education should play an important role in society since it generates and transfers new knowledge and contributes to developing appropriate competencies on this matter. The objective of this paper is to analyse the role played by these components to promote sustainable development. The research method conducted in this work is twofold. First, a conceptualization of the key terms involved in this research was. Next, a constructivist approach centred on the student was conducted to enable the creation of learning proposals to prepare students to take advantage of the possibilities offered by the progress of technology to promote sustainable development and social commerce initiatives. Highlights: ∙ Social economy is rapidly progressing both in human and economic domains. ∙ Collaborative economy is a type of behaviour that contributes to sustainable living. ∙ Virtual currencies play an important role in social commerce and sustainability. ∙ New digital skills need to be added to education curriculums to foster sustainability.